(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
Notaries moved within institutions as both authors of public documents and leading actors. Their involvement as officers can be detected from their own registers, often containing both private deeds and public acts which attest magistrates exercising their functions. This article examines the unpublished registers of Bonvassallo de Olivastro, a notary active in Genoa from 1262 to 1280. The characteristics that emerge from an analysis of his cartularies are here used to chart the evolution of his professional path and the public positions he held at the service of the Genoese Commune’s magistracies. The actors of the deeds allow to map out his vast socialising network, that includes aristocratic families, legal experts and artisans.